Spectral Studies on Hydridophosphine Complexes of Pt-Group Metals: Part-III - Pandey, R.N.; Kumari, Gunjan; Kumar Singh, Rajnish (Asian Journal of Chemistry, 2010)
Mixed-ligand hydridophosphine complexes of Ru(II) and Pt(II) with 1-p-tolyl tetrazoline-5- thione have been prepared and characterized using various physico-chemical studies. Hydridophosphine complexes of Pt(II) are prepared by oxidative addition to Pt(O)-compounds with inorganic acids. Tentative structures are assigned using UV-vis, IR, 1H NMR and other physico-chemical measurements.